2009
DOI: 10.1021/ja8100566
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on Xenon Binding Affinity and Solution Behavior of Water-Soluble Cryptophanes

Abstract: A water-soluble triacetic acid cryptophane-A derivative (TAAC) was synthesized and determined by isothermal titration calorimetry (ITC) and fluorescence quenching assay to have a xenon association constant of 33,000 M−1 at 293 K, which is the largest value measured for any host molecule to date. Fluorescence lifetime measurements of TAAC in the presence of varying amounts of xenon indicated static quenching by the encapsulated xenon and the presence of a second non-xenon-binding conformer in solution. Acid-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
89
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 46 publications
4
89
1
1
Order By: Relevance
“…With a water-soluble triacetate-functionalized cryptophane derivative, a much higher affinity for xenon is observed (K = 33 000 M −1 ). 32 Part of this dramatic increase can be ascribed to a hydrophobic effect of high-energy water 6 inside the cryptophane. With larger solvents such as 1,2-dichlorobenzene, a much higher association constant of K = 2.6 × 10 4 M −1 between the cryptophane 1 (n = 3) and even chloroform was observed.…”
Section: Stacking and Dispersive Interactions In Selected Supramolecumentioning
confidence: 99%
“…With a water-soluble triacetate-functionalized cryptophane derivative, a much higher affinity for xenon is observed (K = 33 000 M −1 ). 32 Part of this dramatic increase can be ascribed to a hydrophobic effect of high-energy water 6 inside the cryptophane. With larger solvents such as 1,2-dichlorobenzene, a much higher association constant of K = 2.6 × 10 4 M −1 between the cryptophane 1 (n = 3) and even chloroform was observed.…”
Section: Stacking and Dispersive Interactions In Selected Supramolecumentioning
confidence: 99%
“…If water is used as solvent, the binding constants can be drastically increased. For example, a water-soluble triacetate-functionalized cryptophane-A derivative shows the highest affinity for xenon which was ever measured for a host molecule (K i ¼ 33,000 M À 1 at 293 K in buffer) 15 . This increase is explained by entropic (hydrophobic) effects that likely involve desolvation of xenon clathrates upon complexation.…”
mentioning
confidence: 98%
“…Recent X-ray crystallographic studies have shown that the internal volume of trisubstituted cryptophane-A derivatives can vary by more than 20%, depending on the size of the encapsulated guest (12). Several cryptophane-A derivatives have been synthesized and shown by isothermal titration calorimetry (ITC), fluorescence quenching, and NMR studies to exhibit xenon association constants as high as 33;000 AE 3;000 M −1 at 293 K in phosphate-buffered water (13)(14)(15)(16). Herein, we report a previously unsynthesized cryptophane-A derivative, tris-(triazole ethylamine) cryptophane (TTEC), with superior xenon-binding characteristics.…”
mentioning
confidence: 99%